1997
DOI: 10.1097/00006454-199704000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ureaplasma urealyticum and Chlamydia trachomatis in development of bronchopulmonary dysplasia in very low birth weight infants

Abstract: C. trachomatis was found infrequently in the airways of premature very low birth weight infants. U. urealyticum was frequently detected but its presence was not significant with regard to development of BPD, duration of ventilatory support, oxygen dependency and length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Of five studies that followed serial cultures, four found an increased risk for BPD among Uu-colonized premature infants, but nasopharyngeal cultures were sometimes used in place of tracheal cultures to determine colonization (13,22,23,34,35). That 20% to 40% of patients may have positive PCRs for Uu with negative cultures also confounds efforts to correlate BPD with colonization by Uu (34,36). Our study demonstrates that approximately 50% of immature baboon infants may clear Uu from their pulmonary system within the first week after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Of five studies that followed serial cultures, four found an increased risk for BPD among Uu-colonized premature infants, but nasopharyngeal cultures were sometimes used in place of tracheal cultures to determine colonization (13,22,23,34,35). That 20% to 40% of patients may have positive PCRs for Uu with negative cultures also confounds efforts to correlate BPD with colonization by Uu (34,36). Our study demonstrates that approximately 50% of immature baboon infants may clear Uu from their pulmonary system within the first week after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were also grouped by definition of BPD, oxygen requirement at 28 days postnatal age (BPD28) and/or 36 weeks postmenstrual age (BPD36). Twenty-three articles reported Ureaplasma colonization and BPD28 (2,6,7,13,45,49,62,89,109,111,123,128,134,137,208,209,215,216,241,247,250,307,329) and eight reported BPD36 (49, 89, 109, 111, 127, 208, 209, 216). There were 2216 infants included in the BPD28 group and 751 infants in the BPD36 group.…”
Section: Association Of Ureaplasma Spp With Development Of Chronic Lmentioning
confidence: 99%
“…This difference can reflect a lower infection rate among our study population or can be due to the low sensitivity of the culture method used. Indeed, we did not use the more sensitive polymerase chain reaction technique (31). Moreover, according to hospital policy, the majority of the mothers with preterm premature rupture of membranes are treated with azithromycin, an agent active against Ureaplasma spp.…”
Section: Mycoplasmataceaementioning
confidence: 99%